2012
DOI: 10.1002/cjce.21682
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of chlorinated organics by hydrotreatment using Ru/TiO2 catalyst

Abstract: Catalytic hydrodechlorination reactions of p‐chloro‐m‐cresol (PCMC) and p‐chloroaniline (PCA) were investigated in a slurry reactor using a Ru/TiO2 catalyst. The organic reaction intermediates, m‐cresol and aniline, were further converted into methylcyclohexanol and cyclohexylamine respectively. Kinetics of PCMC hydrogenation was studied over the ranges in temperature, 323–373 K, H2 partial pressure, 0.34–1.38 MPa, PCMC concentration, 3.5–14 mM and catalyst loading, 0.1–2 kg/m3. The reaction orders with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Both isomers (cis and trans) were identified, being the molar ratio around 70/30 after 4 h reaction time. Other authors have also reported the formation of m-cresol and 3-methyl-cyclohexanone from catalytic HDC of PCMC in aqueous phase with Ru/TiO 2 (5 wt%) [45]. Fig.…”
Section: Hdc Of 246tcp and Pcmcmentioning
confidence: 99%